2023
DOI: 10.3390/diagnostics13182967
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Point-of-Care Monitoring of ALT and AST Is Promising for Faster Decision Making and Diagnosis of Acute Liver Injury

Raja Chinnappan,
Tanveer Ahmad Mir,
Suliman Alsalameh
et al.

Abstract: Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are important liver enzymes in clinical settings. Their levels are known to be elevated in individuals with underlying liver diseases and those consuming hepatotoxic drugs. Serum ALT and AST levels are crucial for diagnosing and assessing liver diseases. Serum ALT is considered the most reliable and specific candidate as a disease biomarker for liver diseases. ALT and AST levels are routinely analyzed in high-risk individuals for the bioanalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…[40][41][42][43][44] ALI is characterized by an early increase in serum levels of aspartate aminotransferase (AST) and lactate dehydrogenase, peaking after a few days, followed by a rise in bilirubin levels on the second or third day. [45][46][47][48] Our investigation revealed that AST (OR=1.002, 95% CI: 1.000-1.003, p=0.01) unequivocally constituted an independent risk factor. AST levels can serve as an objective indicator of liver function in patients with heat stroke.…”
mentioning
confidence: 59%
“…[40][41][42][43][44] ALI is characterized by an early increase in serum levels of aspartate aminotransferase (AST) and lactate dehydrogenase, peaking after a few days, followed by a rise in bilirubin levels on the second or third day. [45][46][47][48] Our investigation revealed that AST (OR=1.002, 95% CI: 1.000-1.003, p=0.01) unequivocally constituted an independent risk factor. AST levels can serve as an objective indicator of liver function in patients with heat stroke.…”
mentioning
confidence: 59%
“…Ideal biosensors are affordable, sensitive, specific, user-friendly, rapid, robust, require no added equipment, and are deliverable to the user [31]. The application of biosensors in the biomedical and bioanalytical fields, especially for biomarker detection and early diagnosis, has increased dramatically over the past decade [32][33][34][35]. Researchers have focused mainly on enhancing the limit of detection (LOD), time-dependent sensitivity, and selectivity of the target analyte.…”
Section: Overview Of Biosensing Technologymentioning
confidence: 99%
“…Historically, finding effective treatments for patients with liver cancers, particularly hepatobiliary cancers, has been challenging due to the lack of appropriate research models. Hence, accurate estimation of the pathophysiology and treatment of hepatic cancer by subtype requires the development of new therapeutic and diagnostic substitutes to address the existing challenges in hepatology research [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%